233k views
5 votes
-5x + 11 = -8(4 + 6x) What are the steps?

User Cryptoplex
by
4.9k points

2 Answers

4 votes
X=1 is the answer to this thank you
User GilLevi
by
5.4k points
7 votes

Answer:


x = - 1

Explanation:


- 5x + 11 = - 8(6x + 4)


= > - 5x + 11 = - 48x - 32

Lets keep the variable terms in L.H.S. and the constant terms in R.H.S.


= > 48x - 5x = - 32 - 11


= > 43x = - 43

Lets divide 43 on both the sides.


= > (43x)/(43) = ( - 43)/(43)


= > x = - 1

User UltimoTG
by
5.1k points